Addressing the difficulty of using the manual accounting system in sales transactions of a real estate project - Gonocruz, Karla Guia P. (Animo Repository, 2017)
This action research paper aimed to address the issue of the difficulty in monitoring and recording sales transactions in one of the projects of the organization, under the real estate company's subsidiary. By conducting interviews with the projects process owners (people who handle the sales transactions in this project), it was identified that using the manual accounting system greatly affects the consistency and productivity of the people, specifically in the Finance Division, where there is a high volume of transactions. It also led to the discovery of many errors when some of the data per Finance records do not match correctly with the supporting documents. It was established through root cause analysis that the inefficiency of the current accounting system of the project is the main cause of the process owners common issue of recording and monitoring difficulty in business transactions. The joint construction of the issue and planning of the action by the team led to the management approval in converting this projects accounting system to SAP by undergoing trainings with outside consultants, testing by the process owners, also doing necessary clean-up of the accounts, and then complying with the BIR requirements to secure approval of using the computerized accounting system. After enacting three action research cycles, the customer accounts were reconciled with the help of the other departments. Process owners were well-trained in using the system after undergoing comprehensive training, and BIR requirements were complied before the release of the permit on using computerized accounting system. Aside from addressing the issue collaboratively, the action research also aimed to improve the working relationships in the Finance Division, establishing more trust among each other when it comes to business transactions. It also highlighted the importance of managing organizational politics and fostering meaningful relationships in order to implement positive change in organizations.